1991
DOI: 10.1136/jech.45.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Body fat distribution in the Finnish population: environmental determinants and predictive power for cardiovascular risk factor levels.

Abstract: Study objective-The aim was to examine (1) whether health habits are associated with body fat distribution, as measured by the waist/hip girth ratio, and (2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
1
8

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(87 citation statements)
references
References 39 publications
6
71
1
8
Order By: Relevance
“…Low social standing, measured here in terms of vocational education, was found to be associated with abdominal obesity, as in earlier studies (Marti et al, 1991;Brunner et al, 1998;Lahmann et al, 2000;Lahti-Koski et al, 2000a). Men who had completed no more than vocational school or an equivalent course had an increased risk even after Model I excludes BMI 31 y, but II includes it.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Low social standing, measured here in terms of vocational education, was found to be associated with abdominal obesity, as in earlier studies (Marti et al, 1991;Brunner et al, 1998;Lahmann et al, 2000;Lahti-Koski et al, 2000a). Men who had completed no more than vocational school or an equivalent course had an increased risk even after Model I excludes BMI 31 y, but II includes it.…”
Section: Discussionsupporting
confidence: 72%
“…All in all, BMI is nevertheless one of the most marked determinants of WHR (Molarius et al, 1999;Lahti-Koski et al, 2000a;Kuh et al, 2002). Apart from its inverse relation to social class (Brunner et al, 1998;Lahmann et al, 2000) and level of education (Marti et al, 1991;LahtiKoski et al, 2000a), WHR has been shown to be associated with several lifestyle factors, such as alcohol consumption (Laws et al, 1990;Sakurai et al, 1997;Dallongeville et al, 1998), smoking (Laws et al, 1990), high intake of dietary saturated fats (Ward et al, 1994), physical inactivity (Laws et al, 1990;Trichopoulou et al, 2001), increased stress and anxiety (Lloyd et al, 1996), shiftwork (van Amelsvoort et al, 1999) and parity (Lahmann et al, 2000). These studies, however, have not taken simultaneously into account earlier lifecourse variables, for example, body size at different ages.…”
Section: Introductionmentioning
confidence: 99%
“…Positive associations between the use of alcohol and abdominal adiposity have consistently been reported for men and frequently for women in cross-sectional (Marti et al, 1991;Troisi et al, 1991;Slattery et al, 1992;Randrianjohany et al, 1993;Dallongeville et al, 1998;Han et al, 1998) or prospective studies (Grinker et al, 1995;Vadstrup et al, 2003;Vernay et al, 2004). Studies showing different results focused on the role of alcohol for the change of anthropometric measures (Koh-Banerjee et al, 2003;Halkjaer et al, 2004Halkjaer et al, , 2006.…”
Section: Discussionmentioning
confidence: 99%
“…However, after puberty, females deposit more fat on the hips and, therefore, WHR becomes significantly lower in females than in males. WHR has a bimodal distribution with relatively little overlap between genders (Marti et al, 1991). The typical range of WHR for healthy premenopausal women has been shown to be .67-.80 (Lanska, Lanska, Hartz,&Rimm, 1985;Marti etal., 1991;O'Brien & Shelton, 1941), whereas healthy men have WHRs in the range of .85-95 (Jones, Hunt, Brown, & Norgan, 1986;Marti et al, 1991).…”
Section: Gender Differences In Body Fat Distributionmentioning
confidence: 99%
“…WHR has a bimodal distribution with relatively little overlap between genders (Marti et al, 1991). The typical range of WHR for healthy premenopausal women has been shown to be .67-.80 (Lanska, Lanska, Hartz,&Rimm, 1985;Marti etal., 1991;O'Brien & Shelton, 1941), whereas healthy men have WHRs in the range of .85-95 (Jones, Hunt, Brown, & Norgan, 1986;Marti et al, 1991). Women typically maintain a lower WHR than men except during menopause when female WHR becomes similar to that of male WHR (Kirschner & Samojilik, 1991).…”
Section: Gender Differences In Body Fat Distributionmentioning
confidence: 99%